2014
DOI: 10.1038/hdy.2013.141
|View full text |Cite
|
Sign up to set email alerts
|

Thank you for not flowering: conservation genetics and gene flow analysis of native and non-native populations of Fraxinus (Oleaceae) in Ireland

Abstract: The risks of gene flow between interfertile native and introduced plant populations are greatest when there is no spatial isolation of pollen clouds and phenological patterns overlap completely. Moreover, invasion probabilities are further increased if introduced populations are capable of producing seeds by selfing. Here we investigated the mating system and patterns of pollen-mediated gene flow among populations of native ash (Fraxinus excelsior) and mixed plantations of non-native ash (F. angustifolia and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…The introduced trees did not have a reproductive advantage over native trees so hybrid genes will not be preferentially spread (Thomasset et al . (). This hybrid is considered undesirable for forestry since F. angustifolia has poorer timber characteristics (Fernández‐Manjarrés et al .…”
Section: Floral and Seed Charactersmentioning
confidence: 97%
See 3 more Smart Citations
“…The introduced trees did not have a reproductive advantage over native trees so hybrid genes will not be preferentially spread (Thomasset et al . (). This hybrid is considered undesirable for forestry since F. angustifolia has poorer timber characteristics (Fernández‐Manjarrés et al .…”
Section: Floral and Seed Charactersmentioning
confidence: 97%
“…The greater distance than recorded by Heuertz et al (2003) was attributed to the more open nature of the fragmented wooded landscape facilitating airborne pollen movement and alleviating the otherwise detrimental genetic effects of population fragmentation. In the open Irish landscape, Thomasset et al (2014) found a mean pollen spread of 260-382 m with a maximum (detected from tree parentage) of >4000 m. However, the relative contribution of pollen and seeds to gene flow within and between populations depends upon whether it is a mast year (Bacles, Lowe & Ennos 2006;Bacles & Ennos 2008); in a mast year, seed dispersal is up to six times more effective in moving genes than pollen dispersal between fragmented populations.…”
Section: ( C ) S E E D P R O D U C T I O N a N D D I S P E R S A Lmentioning
confidence: 98%
See 2 more Smart Citations
“…HÖLTKEN et al, 2003;MORAND et al, 2002;HEUERTZ et al, 2001HEUERTZ et al, , 2003HEUERTZ et al, , 2004aHEUERTZ et al, , 2004bHEUERTZ et al, , 2006HEBEL et al, 2006aHEBEL et al, , 2006bFERRAZZINI et al, 2007;BACLES and ENNOS, 2008;SUTHERLAND et al, 2010;GÖMÖRY et al, 2012), others studies are dealing with gene flow and hybridization (e.g. FERNÁNDEZ-MANJARRÉS et al, 2006;THOMASSET et al, 2013THOMASSET et al, , 2014GÉRARD et al, 2013). In Southern Germany one study on genetic variation of European ash focus on provenance regions (HEBEL et al, 2006b).…”
Section: Genetic Analysis Of European Common Ash (Fraxinus Excelsior mentioning
confidence: 99%